Energetic Particle Radiation Environment Observed by RAD on the Surface of Mars During the September 2017 Event. Issue 11 (14th June 2018) - Ehresmann, B.; Hassler, D. M.; Zeitlin, C.; Guo, J.; Wimmer‐Schweingruber, R. F.; Matthiä, D.; Lohf, H.; Burmeister, S.; Rafkin, S. C. R.; Berger, T.; Reitz, G.
Abstract: The 10–12 September Solar Energetic Particle event produced the strongest increase of the radiation environment measured by the Radiation Assessment Detector on the surface of Mars since landing in August 2012. We report the details of the measurements of the energetic particle environment from Radiation Assessment Detector in Gale crater during this event. The Solar Energetic Particle event increased the low‐energy proton flux (below 100 MeV) by a factor of 30, and the higher‐energy proton flux by a factor of 4, above preevent levels. The 4 He flux (below 100 MeV/nuc) rose by factors up to 10, and neutral particles by a factor of 2 above background. The increase started on 10 September around 19:50 UTC, peak‐level fluxes were reached on the morning of 11 September and prevailed for about 10 hr before decreasing toward background levels. The onset of a Forbush decrease on 13 September decreased the proton flux below preevent intensities. Plain Language Summary: On 10 September 2017, increased solar activity produced a solar energetic particle (SEP)event. This SEP event arrived at Mars around UTC 20:00 the same day in form of energetic particles accelerated to high enough energies to reach the Martian surface. We report here measurements of the energetic particle environment during the event in Gale crater on Mars, made with the Radiation Assessment Detector on board NASA's Curiosity rover. The SEPs increased the Martian surface proton flux below 100‐MeV energy by a factor of 30, and by a factor of 4 at higher energies. The neutral particle environment doubled during the event, which is of particular interest for the planning of solar storm shelters, as the shielding is less effective against neutrons as it is against charged particles. The increase in proton flux was the highest so far observed by Radiation Assessment Detector since landing on Mars in August 2012. However, stronger SEP events are possible that can increase the Martian radiation environment by orders of magnitude more. This makes monitoring the effect of SEPs crucial as radiation remains one of the major health risks for astronauts on exploration missions. Key Points: On 11 September 2017, RAD observed the strongest solar particle event on the Martian surface since landing Proton fluxes at the Martian surface increased by factors of up to 30, helium fluxes by factors up to 10 Doubling of neutral particle counts is important for planning of future storm shelter shielding, which is not as effective against neutrons